Microbiological and serological monitoring in hooded crow (Corvus corone cornix) in the Region Lombardia, Italy - Guido Grilli; Daniele Gallazzi; Davide Lelli; Ana Moreno Martin; Viviana Ferrazzi (Italian Journal of Animal Science, 2010)
The health status of 276 hooded crows (Corvus corone cornix) from various provinces of Lombardy was monitored for three years. Bacteriological examination detected E. coli (76%), Campylobacter jejuni (17%), Salmonella typhimurium (11.6%), Yersinia spp. (6.5%), Clamydophila abortus and C. psittaci (2.6%); from six birds showing severe prostration Pasteurella multocida was isolated. Virological and serological tests were negative for Avian Influenza virus (AIV), West Nile virus (WNV) and only three samples were positive for Newcastle disease virus (NDV) but only at serology (titre 1:16).